2015
DOI: 10.1080/01621424.2015.1029185
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Home Care Management on the Involvement of Informal Caregivers by Formal Caregivers

Abstract: This study explores the link between management characteristics of home care agencies and the involvement of informal caregivers in caregiving. Based on a study of policy documents of two agencies and semi-structured interviews with five team managers and 31 formal caregivers, we conclude that, although the importance of involving informal caregivers is emphasized in official documentation, actual contact with informal caregivers is often lacking. Comparison of the work processes of the two agencies shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 33 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…The relatives in our study expected more information from the reablement team than what was given. These findings are confirmed by several researchers,10,12,16,28,29 who argue that how the role as the relative in health care is handled is strongly associated with the opportunity to obtain information. Studies by Glendinning et al19 and Wilde and Glendinning2 revealed that family caregivers felt more confident in their caring responsibilities when information about the management of daily routines was passed on from the reablement team and when advice related to their own needs was given.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The relatives in our study expected more information from the reablement team than what was given. These findings are confirmed by several researchers,10,12,16,28,29 who argue that how the role as the relative in health care is handled is strongly associated with the opportunity to obtain information. Studies by Glendinning et al19 and Wilde and Glendinning2 revealed that family caregivers felt more confident in their caring responsibilities when information about the management of daily routines was passed on from the reablement team and when advice related to their own needs was given.…”
Section: Discussionsupporting
confidence: 66%
“…Although the importance of involving informal caregivers is highlighted in official documents, research points out that health care professionals contact and collaboration with informal caregivers is often lacking 1014. In the study of van Wieringen et al,10 “professionals generally regard caregivers as ‘coworkers’ because both parties perform comparable tasks”.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is increasingly expected that they integrate informal caregiver involvement in formal work processes. Results of a study of two agencies and their clients in the Netherlands [16] show that the nurses were aware of the organizational policy which stated that they should proactively keep connected with informal caregivers. But most of them acknowledge that they hardly ever did so.…”
Section: Online Care Networkmentioning
confidence: 99%